Prior intracerebral hemorrhage and white matter hyperintensity burden on recurrent stroke risk - Jong-Ho Park (Nature Portfolio, 2021)
Abstract Prior intracerebral hemorrhage (ICH) is associated with increased risk of ischemic stroke. Since white matter hyperintensity (WMH) is associated with ischemic stroke and ICH, this study aimed to evaluate the relationship between ICH and the risk of recurrent stroke by WMH severity. From a prospective multicenter database comprising 1454 noncardioembolic stroke patients with cerebral small-vessel disease, patients were categorized by presence or absence of prior ICH and WMH severity: mild-moderate WMH (reference); advanced WMH; ICH with mild-moderate WMH; and ICH with advanced WMH. Among patients with ICH, the association with stroke outcomes by WMH burden was further assessed. The primary endpoint was ischemic stroke and hemorrhagic stroke. The secondary endpoint was major adverse cardiovascular events (MACE): stroke/coronary heart disease/vascular death. During the mean 1.9-year follow-up period, the ischemic stroke incidence rate per 100 person-years was 2.7, 4.0, 2.5, and 8.1 in increasing severity, and the rate of hemorrhagic stroke was 0.7, 1.3, 0.6, and 2.1, respectively. The risk of ischemic stroke was higher in ICH with advanced WMH (adjusted HR 2.62; 95% CI 1.22−5.60) than the reference group, while the risk of hemorrhagic stroke trended higher (3.75, 0.85–16.53). The risk of MACE showed a similar pattern in ICH with advanced WMH. Among ICH patients, compared with mild WMH, the risk of ischemic stroke trended to be higher in advanced WMH (HR 3.37; 95% CI 0.90‒12.61). Advanced WMH was independently associated with an increased risk of hemorrhagic stroke (HR 33.96; 95% CI 1.52−760.95). Given the fewer rate of hemorrhagic stroke, the risk of hemorrhagic stroke might not outweigh the benefits of antiplatelet therapy for secondary prevention.